Predictive validity of the Hand Arm Risk assessment Method (HARM) - Douwes, M.; Boocock, M.; Coenen, Pieter; van den Heuvel, S.; Bosch, T. (2014)
The Hand Arm Risk assessment Method (HARM) is a simplified risk assessment method for determining musculoskeletal symptoms to the arm, neck and/or shoulder posed by hand-arm tasks of the upper body. The purpose of this study was to evaluate the predictive validity of HARM using data collected from a three year prospective cohort Study on Musculoskeletal disorders, Absenteeism and Health (SMASH). Structured observations of video recordings using HARM were made of 88 participants performing hand-arm tasks. These video recordings were made at baseline of the SMASH study, whereas self-reported musculoskeletal symptoms were assessed both at baseline and during a three year follow-up. The receiver operating characteristic (ROC) curves showed an area under the curve (AUC) of 0.75 (CI: 0.65-0.86) for symptoms at baseline and 0.70 (CI: 0.58-0.83) for symptoms during follow-up. For a HARM score of 50, the sensitivity and specificity were 64% and 79% at baseline and 53% and 82% during follow up. Participants with a HARM score of 50 or more (considered a high risk) had a significantly higher risk of upper limb symptoms than those with a HARM score of less than 50 at baseline (OR=5.31; 95%CI: 2.10-13.39) and 3 year follow-up (OR=5.11; (95%CI: 1.61-16.27). This study has shown that HARM can be used to assess work tasks of the hands and arms and discriminate between tasks that pose a high or low risk of neck or upper limb symptoms. Relevance to industry: The association of HARM results and self-reported neck and upper limb symptoms was studied. The association found both cross sectionally and at follow up shows that the method can be used in industry to distinguish hazardous hand arm tasks from non-hazardous ones. Thus, HARM can support OSH practitioners and industrial engineers in designing healthy workplaces. © 2013 Elsevier B.V.